Transforming Early Childhood Education Management: Integrating Technology and Holistic Approaches - Said Maskur; Hasyamuddin Bin Othman (DZURRIYAT : Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Transforming early childhood education (ECE) management has become an essential effort to address the challenges of 21st-century education. This study aims to analyze transformative ECE management strategies by integrating digital innovation, holistic approaches, and transformational leadership to establish adaptive and sustainable institutional models. The research employed a qualitative descriptive design with data collected through interviews, observations, and document analysis across several ECE institutions that have adopted digital management systems and holistic curricula. The findings show that the integration of digital technology enhances management effectiveness, facilitates personalized learning, expands parental participation, and strengthens stakeholder collaboration. Furthermore, holistic approaches positively influence children’s cognitive, emotional, social, and physical development, while transformational leadership emerges as a key driver for fostering innovation, improving service quality, and ensuring institutional sustainability.